P068 Improving patient streaming for Chronic insomnia: Single centre retrospective cohort study. (7th October 2021) - Krebs, L; Ellender, C
Abstract: Background: Insomnia is a common sleep disorder associated with significant morbidity and psychological distress. Cognitive Behavioural Therapy for insomnia (CBTi) is the gold standard intervention typically delivered by sleep psychologists. High demand has driven an interest in determining the case mix and characteristics of patients referred with insomnia to identify patients that may be suitable for an alternative direct-to-psychology model of care. Methods: A retrospective cohort study was performed, including cases referred to the Princess Alexandra Hospital Sleep Centre in 2016 – 2020. Patients were categorised as either "suitable for direct-to-psychology" or "required medical review". "Direct to psychology" patients were defined as (i) referred for insomnia; or (ii) Insomnia Severity Index score ≥15/28; or (iii) diagnosed with insomnia per ICSD-3 by treating specialist; or (iv) patients referred for sleep psychology. Exclusion criteria were significant sleep disordered breathing (mean SpO2 <85%, Epworth sleepiness scale >16, driving inattention), highly co-morbid patients (neuromuscular weakness, COPD) and diagnosis of hypersomnia. These patients were categorised as "requiring medical review". The demographic and polysomnographic characteristics of these two groups were then compared. Progress: The study protocol is complete, ethical approval obtained (EX/2021QMS/76783), and data extraction has been competed. Analysis underway currently. Intended outcome/impact: We aim to establish the characteristics of patients suitable for a direct to psychology pathway. This data will be used for service provision planning, could reduce patient waiting list times, and improve patient care. This model could then be explored for safety and efficacy and form the basis of future service provision work.